BADAL HAJI - Abdul Malik (Universitas Islam Negeri Sumatera Utara, 2016)
In the implementation of the pilgrimage is known as the substitution that is replaced in the intention of replacing someone else carry out the pilgrimage. The fact is most people are very easy to replace haji others others. Badal was a substitute (particularly for the Hajj); the representative; performing the Hajj pilgrimage to replace others like replacing the deceased person or the representative of the Hajj